2018
DOI: 10.1038/s41426-018-0059-4
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of Leptospira in wild animal communities inhabiting the insular ecosystem of the western Indian Ocean islands and neighboring Africa

Abstract: Understanding the processes driving parasite assemblages is particularly important in the context of zoonotic infectious diseases. Leptospirosis is a widespread zoonotic bacterial infection caused by pathogenic species of the genus Leptospira. Despite a wide range of animal hosts, information is still lacking on the factors shaping Leptospira diversity in wild animal communities, especially in regions, such as tropical insular ecosystems, with high host species richness and complex biogeographical patterns. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 50 publications
(91 reference statements)
2
58
1
Order By: Relevance
“…For M. natalensis , among the bats sampled at two ( n = 85) or three ( n = 30) body habitats, 45% were infected by two infectious agents and 17% were infected by the three infectious agents. Leptospira -positive urine samples in M. natalensis clustered in two genetic groups ( figure 2 a ), one associated with L. borgpetersenii samples previously identified in M. natalensis in South Africa [ 26 ] and the other closely related to L. interrogans and L. kirschneri . High Leptospira shedding prevalence was observed across the reproductive season, varying between 71% (±18%) and 87% (±10%).…”
Section: Resultsmentioning
confidence: 92%
“…For M. natalensis , among the bats sampled at two ( n = 85) or three ( n = 30) body habitats, 45% were infected by two infectious agents and 17% were infected by the three infectious agents. Leptospira -positive urine samples in M. natalensis clustered in two genetic groups ( figure 2 a ), one associated with L. borgpetersenii samples previously identified in M. natalensis in South Africa [ 26 ] and the other closely related to L. interrogans and L. kirschneri . High Leptospira shedding prevalence was observed across the reproductive season, varying between 71% (±18%) and 87% (±10%).…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies noticed that MLST approaches may contribute to unravel potential associations between specific Leptospira STs and their hosts and geographic regions of origin (Boonsilp et al, ; Dietrich et al, , ). For example, Dietrich et al () found a distinct clustering of Leptospira isolates according to their different small mammal host species in Madagascar.…”
Section: Discussionmentioning
confidence: 99%
“…This zoonosis is estimated to cause more than one million human cases and 58,900 deaths each year ( 1 ). Disease incidence is highest on tropical islands, notably in the southwestern Indian Ocean, where investigations carried out under a One Health framework have revealed distinct transmission chains in the different islands ( 2 5 ), including the occurrence of Leptospira mayottensis , a pathogenic Leptospira species recently recognized as new to science ( 6 ). Representatives of L. mayottensis (formerly known as Leptospira borgpetersenii group B) were originally isolated from human acute cases ( 7 ) and later identified in tenrecs ( 2 , 5 , 8 ), a diversified family of mammals endemic to Madagascar ( 9 , 10 ).…”
Section: Announcementmentioning
confidence: 99%
“…Three L. mayottensis strains were isolated in the field from two tenrec species, namely, Tenrec ecaudatus on Mayotte (MDI222 and MDI272) ( 2 ) and Microgale dobsoni on Madagascar (VS2413) ( 5 ). Frozen isolates were thawed in liquid Ellinghausen-McCullough-Johnson-Harris (EMJH) medium containing albumin fatty acid supplements (AFAS) ( 3 ), and they were further subcultured in EMJH supplemented with AFAS, 1% fetal calf serum, and 8% rabbit serum.…”
Section: Announcementmentioning
confidence: 99%